Identification of Ectoparasites in Sharks at the Paotere Makassar Fish Landing Base - Andi Simpur; Toliu, Wudhia Windy; Mappiara, Muhammad Afiq S.; Nurdin, Muhammad Ardiansyah (Media Kedokteran Hewan, 2025)
Sharks are predators in aquatic ecosystems that play a crucial role in maintaining the balance of the ecosystem. The existence of sharks has become a topic of discussion in fisheries institutions due to the increase in shark hunting activities, especially for consumption. Disease problems in sharks, especially those caused by parasites, can lead to a decline in shark quality and have a negative impact on human health. This study aims to identify ectoparasites found on sharks at the Paotere Makassar Fish Landing Base. The method of this study involves collecting 11 shark samples, including mucus on the surface of the shark skin and organ mucus from the gills, randomly from 5 species of sharks. Parasite examination was carried out in the laboratory by adding a physiological NaCl solution to the sample, which was then placed on a glass slide before identification under a microscope. The results of this study showed the presence of parasites, including Trichodina sp., Chilodonella sp., and Anisakis sp.